Compression Of 2-D And 3-D Signals For Telemedicine Applications - Shyamsunder , Regunathan (2006)
The amount of medical data such as magnetic resonance (MR) images, X-ray Angiograms(XA) and patient videos generated in hospitals has been increasing rapidly in the recent years. This research work deals with the lossy compression of 2D and 3D signals for telemedicine applications. In particular, the compression of (i) 2D MR and XA images (ii) 3D MR and XA images ( i.e sequential slices of the images) and (iii) patient videos is considered.